COINFECÇÃO COVID-19-TB: CARACTERÍSTICAS EPIDEMIOLÓGICAS NA CAPITAL DE MATO GROSSO DO SUL - Ana Carulina Guimaraes Belchior (2024)
Tuberculosis and COVID-19 are global public health problems and are the leading causes of death due to infectious agents. Understanding the interaction between these pathogens becomes relevant as it can contribute to guiding actions aimed at reducing morbidity and mortality in this scenario. Objective: To evaluate the epidemiological characteristics of the COVID-19-TB comorbidity in Campo Grande city during the first two years of the pandemic. Methods: A non-paired case-control study with retrospective data collection in eight hospitals in Campo Grande, from March 2020 to March 2022. Twenty-one hospitalized cases of COVID-19-TB coinfection (case group) and 21 hospitalized cases of COVID-19 without TB (control group), confirmed by laboratory tests, were selected. Association analysis between variables and binary logistic regression were used, with a statistical significance level of p≤0.05. Results: The COVID-19-TB comorbidity was frequently associated with HIV infection, which did not impact the lethality . Coinfected patients had fewer cases of dyspnea, a lower need for mechanical ventilation, and less ground-glass opacity on imaging compared to cases with only COVID-19. On the other hand, they more frequently showed a tomographic pattern of centrilobular micronodules, higher levels of C-reactive protein, and lower hemoglobin levels, with the latter variable being independently associated with TB. Conclusion: TB should be suspected in all patients with COVID-19, and investigated especially those with reduced hemoglobin. In the presence of tomographic patterns showing ground-glass opacities and centrilobular micronodules, the presence of infection by the SARS-CoV-2 coronavirus and Mycobacterium tuberculosis should be assessed.